THE INCIDENCE OF MUSCULOSKELETAL DISEASES IN THE RUSSIAN FEDERATION OVER 2015–2016 - R. M. Balabanova; T. V. Dubinina; A. V. Demina; O. A. Krichevskaya (Научно-практическая ревматология)
Objective: to assess trends in the overall and primary incidence of rheumatic diseases (RD) from by visit rates in Russia in 2015–2016.Material and methods. The incidence rates were analyzed on the basis of the data presented in the reports of the Ministry of Health of Russia on adult mortality rates in 2015 and 2016.Results and discussion. The analysis of adult morbidity rates associated with musculoskeletal diseases (MSDs) revealed a certain downward trend in Russia over 2015–2016. The total number of registered patients with this pathology in 2016 amounted to 16.6 million people, which were 266 thousand people less than in 2015. The primary incidence of MSDs showed a decline by 55 thousand people in this period. The reports of the Ministry of Health indicate that the entire group of patients with MSDs in the section «Rheumatology» has data on six nosological entities: rheumatoid arthritis (RA), reactive arthropathies (RAP), spondylopathies (SP), systemic connective tissue disease (SCTD), osteoarthritis (OA), and osteoporosis (OP). In the RD group OA accounted for the highest incidence rates (4,350,465 cases in 2015 with some reduction (4,285,464 cases) in 2016). In 2015 and 2016, the incidence of RA was 50,905 and 76,823 cases; that of SP was 110,855 and 115,442 cases; that of RAP was 50,905 and 76,823 cases; that of SCTD was 62,265 and 58,276 cases; that of OP was 155.107 and 155,624 cases, respectively. psoriatic arthritis (PsA) accounted for the lowest incidence rates (18,069 and 19,229 cases). The Russian Federation annually registers more than 600 primary cases of OA per 100,000 adult population; less frequent were RA (27.2), SP (18.2), OP (10.2), and RAP (13.5); SCTD and PsA were much less diagnosed (5.9 and 2.84, respectively). Noteworthy are significant variations in the overall and primary incidence in both federal districts and one federal district, making it difficult to attribute only to climatic and geographical factors. This is most likely to be associated with a shortage of trained rheumatologists in individual subjects of the Russian Federation. In addition, it is necessary to monitor the correctness of the diagnosis and its encoding in accordance with ICD-10.